New essays on Billy Budd - Yannella, Donald (American novel., 2002)
"Billy Budd is Herman Melville's most read work after Moby-Dick, and it is regularly taught in literature courses of all kinds. Melville wrote the novella during the five years before his death, and it was published posthumously in 1924. The essays collected here investigate Billy Budd in the context of nineteenth-century political and social dynamics and the literary response they provoked, as well as the relevance of mythology and the histories of the classical world and Judaeo-Christian civilization to Melville's book. Also examined are Melville's later writing, including the late poetry; the text's development; and its ambiguities. The collection will prove an invaluable resource for students of this major American writer."--Jacket